Kajian Jenis-jenis Kayu dan Perhitungan Volume Bahan Pembuatan Kapal Nelayan Tradisional di Kecamatan Bangkurung Kabupaten Banggai Laut - Bidullah, Umi Kalsum; Salam, Azis; Fachrussyah, Zhulmaydin Chairil (The NIKe Journal, 2025)
This study aims to determine the types of wood used in making traditional boats and to determine the calculation of the volume of materials needed for making traditional fishing boats in Kalupapi Village and Bone-Bone Village, Bangkurung District, Banggai Laut Regency. The research method used a survey method applied in two ways, namely interviews using questionnaires and direct sample measurements. The results of this study indicate that traditional fishing boats in Kalupapi Village and Bone-Bone Village are made of wood, which not only provides strength and durability, but also supports environmental sustainability by utilizing natural resources available around the village. The types of wood used are meranti wood and ironwood. To calculate the estimated wood requirements in boat construction, which include the volume of boards and the length and diameter of the mahera, the board volume coefficient (Cp), the mahera length coefficient (Clm), and the mahera diameter coefficient (Cd) can be used. In this study, the results obtained are Cp 0.1604, Clm 9.300, and Cd 0.498.